Pengaruh Pupuk Kandang Ayam dan Pupuk Urea Terhadap Pertumbuhan dan Hasil Tanaman Sawi Pakcoy (Brassica annum L.) - Hulu, Yusnita Dewi; Zulfida, Ida; Harahap, Lutfi Henderlan (JURNAL AGROPLASMA, 2024)
This study aims to analyze the effect of using chicken manure and urea fertilizer on the growth and production of pakcoy (Brassica rapa L.). This study used an experimental method with a randomized complete block design (RCBD) consisting of two main factors, namely the dose of chicken manure and urea fertilizer. The doses of chicken manure used were 2 kg/plot and 4 kg/plot, while the doses of urea fertilizer used were 15 g/plot and 20 g/plot. The parameters observed included plant height, number of leaves, leaf area, fresh weight per plant, and fresh weight per plot. The results showed that the combined use of chicken manure and urea fertilizer had a significant effect on pakcoy growth parameters, especially plant height, number of leaves, leaf area, and fresh weight per plant. Keywords: chicken manure, urea fertilizer, pakcoy